Ketika Kecerdasan Buatan Menjadi Alat Kecurangan Tingkat Lanjut: Tantangan dan Peran Kepribadian Mahasiswa - Ahmadi Sasmi, Aji; Ikhwan, Muhammad; Gurendrawati, Etty; Suherdi, Suherdi; Rulita Nurfaizana, Della (Jurnal Riset Pendidikan Ekonomi, 2024)
This study aims to explore the influence of personality traits, specifically Agreeableness, Conscientiousness, and Emotionality, on students' tendencies toward cheating behavior, analyzed using artificial intelligence (AI). A quantitative approach was employed, with data collected through a Likert-scale questionnaire completed by students from the Faculty of Economics at a university in Jakarta. Using simple random sampling and data analysis with SmartPLS, this research examines the relationships among variables to gain a deeper understanding of the role of personality factors in unethical behavior. The findings reveal that Agreeableness does not significantly impact cheating tendencies, whereas Conscientiousness and Emotionality show significant effects. Students with high Conscientiousness levels tend to have better self-control, thus reducing the likelihood of cheating. Conversely, Emotionality influences this behavior, indicating that emotional management plays a crucial role in ethical decision-making. These findings imply the need for educational strategies that emphasize not only discipline but also emotional regulation, in order to foster academic integrity within higher education environments.